Synthesis and Spectroscopic Studies of Dichloromono-(1-n-butylamidino-Omethylurea) copper(II), Dichloromono(1-i-butylamidino-O-methylurea)copper(II) and Dichloromono-(1-i-butylamidino-O-ethylurea)copper(II) Complexes - Ibopishak Singh, O.; Bimola Devi, A.; Hemakumar Singh, R.K.; Kadam, R.M. (Asian Journal of Chemistry, 2010)
Electron paramagnetic resonance studies of dichloro(1- n-butylamidino-O-methylurea)copper(II) (1), dichloro(1-i-butylamidino- O-methylurea)copper(II) (2) and dichloro(1-i-butylamidino- O-ethylurea)copper(II) (3) complexes were carried out in the temperature range 300-77 K. In complexes 1 and 2 apart from a strong signal at g ~ 2.0711 a weak half field signals (ΔMs = ± 2) were also observed suggesting the formation of dimeric complexes. The photo acoustic spectra of the complexes had shown a band around 25000 cm-1 suggesting weak metal-metal interactions. The EPR spectral features of complex 3 are characteristic of axial symmetry and the hyperfine structure on parallel components of Cu2+ species is resolved. The EPR spectra at 77 K in pyridine has shown axial ligation of solvent molecules. The high magnetic moment values of complexes 1 and 2 had given evidence for the formation of ferromagnetically coupled Cu2+ dimers.